2015
DOI: 10.1144/sp427.9
|View full text |Cite
|
Sign up to set email alerts
|

Lower–Middle Jurassic facies patterns in the NW Afghan–Tajik Basin of southern Uzbekistan and their geodynamic context

Abstract: Based on eleven sections, the palaeoenvironments and depositional history of the northwestern Afghan-Tajik Basin in southern Uzbekistan have been reconstructed for the time interval Early Jurassic to Early Callovian. The earliest sediments, resting on Palaeozoic basement rocks, date from the Early Jurassic Period. Up to the end of the Early Bajocian time up to more than 500 m of non-marine sediments accumulated due to extensional tectonics inducing active subsidence. In the Late Bajocian time interval, transgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The Jurassic‐Cretaceous cooling recorded in the western Tian Shan likely is the vestige of widespread crustal extension after the “Eo‐Cimmerian” (Norian‐Rhaetian) orogeny, best documented in Uzbekistan and Iran. Extension almost ceased at the end of the Middle Jurassic (~160 Ma), with only minor normal faulting recorded in Upper Jurassic and Cretaceous strata; this time was mostly characterized by thermal subsidence (e.g., Brunet et al, 2017; Fürsich et al, 2015; Mordvintsev et al, 2017). For the often cited trigger of the cooling by collisions at the southern margin of Asia (e.g., De Grave et al, 2012, 2013; Glorie et al, 2011; Jepson, Glorie, Konopelko, Gillespie, et al, 2018), we see no structural evidence in the studied areas.…”
Section: Discussionmentioning
confidence: 99%
“…The Jurassic‐Cretaceous cooling recorded in the western Tian Shan likely is the vestige of widespread crustal extension after the “Eo‐Cimmerian” (Norian‐Rhaetian) orogeny, best documented in Uzbekistan and Iran. Extension almost ceased at the end of the Middle Jurassic (~160 Ma), with only minor normal faulting recorded in Upper Jurassic and Cretaceous strata; this time was mostly characterized by thermal subsidence (e.g., Brunet et al, 2017; Fürsich et al, 2015; Mordvintsev et al, 2017). For the often cited trigger of the cooling by collisions at the southern margin of Asia (e.g., De Grave et al, 2012, 2013; Glorie et al, 2011; Jepson, Glorie, Konopelko, Gillespie, et al, 2018), we see no structural evidence in the studied areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are limited studies on the sedimentological characteristics of the Shurijeh-Shatlyk formations, particularly in the eastern part of the basin (Turkmenistan, Uzbekistan, and Afghanistan), recent studies on the Kopeh Dagh Foldbelt have indicated that the Shurijeh-Shatlyk formations were deposited in arid to semiarid climatic conditions in palaeolatitudes of about 30°to 40°N (Fursich, Brunet, Auxie'tre, & Munsch, 2015;Mortazavi, Moussavi-Harami, Brenner, & Mahboubi, 2013;Moussavi-Harami, Mahboubi, Nadjafi, Brenner, & Mortazavi, 2009;Thomas, Cobbold, Shein, & Le Douaran, 1999). In addition, Moussavi-Harami and Brenner (1990) suggested that the siliciclastic sediments of the Shurijeh Formation have metamorphic, igneous and sedimentary sources that derived from south and south-west of Mashhad (i.e., north-east Iran).…”
Section: Synrift Sediments Rest With An Angular Unconformity On Devonmentioning
confidence: 99%
“…Stampfli & Borel 2002;Barrier & Vrielynck 2008, 2017Wilmsen et al 2009;Zanchi et al 2009Zanchi et al , 2012, a number of new or rejuvenated sedimentary basins formed north of the main collision zone in Central Asia, including the Amu Darya Basin (extending mainly across Turkmenistan and Uzbekistan) and the Afghan-Tajik Basin (extending across Uzbekistan, Tajikistan and Afghanistan) (e.g. Thomas et al 1999a;Melikhov 2000Melikhov , 2013Melikhov , 2017Brookfield & Hashmat 2001;Ulmishek 2004;Klett et al 2006;Fü rsich et al 2015;Brunet et al 2017). The evolution of these two basins was closely linked from the Late Palaeozoic onwards; indeed, during Jurassic times the two basins were connected.…”
Section: Geological Evolution Of Central Asian Basins and The Westernmentioning
confidence: 99%
“…The Jurassic -Cretaceous was characterized by a general planation of the previously formed relief (e.g. Makarov 1977;Chediya 1986;Burbank et al 1999;Allen et al 2001;Cunningham et al 2003;Jolivet et al 2010Jolivet et al , 2013Jolivet et al , 2015, providing sediments to these newly forming extensional basins (Brookfield & Hashmat 2001;Klett et al 2006;Fü rsich et al 2015;Brunet et al 2017).…”
Section: Geological Evolution Of Central Asian Basins and The Westernmentioning
confidence: 99%
See 1 more Smart Citation